A Novel Iterative Method for Polar Decomposition and Matrix Sign Function - F. Soleymani; Predrag S. Stanimirović; Igor Stojanović (Discrete Dynamics in Nature and Society)
We define and investigate a globally convergent iterative method possessing sixth order of convergence which is intended to calculate the polar decomposition and the matrix sign function. Some analysis of stability and computational complexity are brought forward. The behaviors of the proposed algorithms are illustrated by numerical experiments.